Voices of Atayal People: Indigenous Cultural Memory in Modern Taiwan Society - Thao, Yer J. (Advances in Social Sciences Research Journal, 2019)
When talking about Indigenous culture in the 21st century, it is important to understand the Taiwan Indigenous People and their ways of cultural practices. This study used ethnographic inquiry as a qualitative approach for a total of 11 people from an aboriginal tribe called, Tayal (Atayal) in northern Taiwan. Data sources include: (1) Tape-recording in Mandarin Chinese, Tayal language, and English from the research participants; (2) Community event observations; and (3) one-on-one interviews. This study revealed that preservation of Tayal heritage, language, culture and social lifestyle structure in the 21st century and beyond is a major concern and deeply important to Tayal communities and individuals. An effort to construct an authentic Tayal traditional culture education program seems to have significant benefits for not only Tayal children, families, communities, but for the Taiwanese society as well.